Pengaruh Penilaian Prestasi Kerja, Kompetensi Karyawan dan Pengalaman Kerja terhadap Promosi Jabatan pada Lembaga Amil Zakat Nasional Nurul Hayat Surabaya: The Effect of Job Performance Assessment, Employee Competence and Work Experience on Position Promotion at the National Amil Zakat Institute Nurul Hayat Surabaya - Prasetyo, Totok Dwi; Hariasih, Misti; Sari, Herlinda Maya Kumala (Universitas Muhammadiyah Sidoarjo, 2017)
This study aims to determine the effect of Job Performance, Employee Competence and Experience Work Campaign Against Occupation At the Institute National Zakat Nurul Hayat Surabaya. The analytical method used in this research is the analysis of the ratio and difference test by using multiple linear regression analysis. The calculation result of F test performed with SPSS version 17 above , the F value calculated at 140 376 . So that the calculated F value is greater than the F table is 2,53 significance value obtained was 0,000 , so the significance value is less than the value of α is 0.05 . Because ( F count> F table = ( 140 376 > 2.53 ) and ( sig < α = 0.000 < 0.05 ) . So there is a significant influence variables Job Performance , Employee Competence and Experience Work Campaign Against the Occupation . Based on the results of T test showed that the variables affect the Job Performance Job Promotion, Promotion influential Variable Position Employee Competence , Work Experience Further variables affect the Promotion Department.